First evidence of denitrification vis-à-vis monsoon in the Arabian Sea since Late Miocene - Tripathi, Shubham; Tiwari, Manish; Lee, Jongmin; Khim, Boo-Keun; Pandey, Dhananjai K.; Clift, Peter D.; Kulhanek, Denise K.; Andò, Sergio; Bendle, James A.P.; Aharonovich, Sophia; Griffith, Elizabeth M.; Gurumurthy, Gundiga P.; et al. (Springer Nature, 2017)
In the Arabian Sea, South Asian monsoon (SAM)-induced high surface water productivity coupled with poor ventilation of intermediate water results in strong denitrification within the oxygen minimum zone (OMZ). Despite the significance of denitrification in the Arabian Sea, we have no long-term record of its evolution spanning the past several million years. Here, we present the first record of denitrification evolution since Late Miocene (∼10.2 Ma) in the Eastern Arabian Sea, where the SAM generates moderate surface water productivity, based on the samples retrieved during the International Ocean Discovery Program (IODP) Expedition 355. We find that (i) the SAM was persistently weaker from ∼10.2 to 3.1 Ma; it did not intensify at ∼8 Ma in contrast to a few previous studies, (ii) on tectonic timescale, both the SAM and the East Asian Monsoon (EAM) varied synchronously, (iii) the first evidence of denitrification and productivity/SAM intensification was at ∼3.2-2.8 Ma that coincided with Mid-Pliocene Warm Period (MPWP), and (iv) the modern strength of the OMZ where denitrification is a permanent feature was attained at ∼1.0 Ma.